Interfacial catalysis in and initial reaction mechanism of Al2O3 films fabricated by atomic layer deposition using non-hydrolytic sol–gel chemistry. Issue 45 (7th November 2016) - Xu, Lina; Fang, Guoyong; Cao, Yanqiang; Li, Aidong
Abstract : DFT investigation shows that metal alkoxides can directly form M–O bonds through strong chemisorption and interfacial interactions between alkyl groups and the surface can catalyze the elimination of alkyl groups through interfacial catalysis. Abstract : Atomic layer deposition (ALD) is a powerful nanofabrication technique that can precisely control the composition, structure, and thickness of thin films at the atomic scale, and is widely used in the fields of electronic displays, microelectronics, catalysis, coatings, and energy storage and conversion. ALD of metal oxide thin films can be completed using metal alkoxides as the oxygen source, which is similar to the non-hydrolytic sol–gel (NHSG) technique. Density functional theory calculations show that metal alkoxides, such as Al(O i Pr)3 and Al(OEt)3, can directly form M–O bonds through strong chemisorption on the surface. Meanwhile, alkyl groups can be eliminated through the formation of alkyl halides and alkenes, which can be catalyzed by interfacial interactions between alkyl groups and the surface. Such noncovalent catalysis resulting from interfacial interaction can be termed as interfacial catalysis. This can be characterized by the difference between the interfacial interaction energies of the transition state and the corresponding intermediate based on natural bond analysis. We expect that such interfacial catalysis can be used in precursor designs, improvement of ALD of oxides and as a new characterization method for other interfacial catalysis and noncovalent catalysis processes.